Connexin 43 Differentially Regulates Epileptiform Activity in Models of Convulsive and Non-convulsive Epilepsies - Vincze, Renáta; Péter, Márton; Szabó, Zsolt; Kardos, Julianna; Héja, László; Kovács, Zsolt (Frontiers in Cellular Neuroscience, 2019)
The influence of astrocytic cell networks on neuronal network activity is an emerging issue in epilepsy. Among the various mechanisms by which astrocytes modulate neuronal function, synchronization of astrocytes via gap junction channels is widely considered to be a crucial mechanism in epileptic conditions, contributing to the synchronization of the neuronal cell networks, possibly inducing recurrent epileptiform activity. Here we explored whether modulation of astrocytic gap junctions could alter epileptic seizures in different types of epilepsy. Opening of gap junctions by trimethylamine intensifies seizure-like events in the low-[Mg2+] in vitro model of temporal lobe epilepsy, while alleviates seizures in the in vivo WAG/Rij rat model of absence epilepsy. In contrast, application of the gap junction blocker carbenoxolone prevents the appearance of seizure-like events in the low-[Mg2+] epilepsy model, but aggravates seizures in non-convulsive absence epilepsy, in vivo. Pharmacological dissection of neuronal vs. astrocytic connexins shows that astrocytic Cx43 contribute to seizure formation to a significantly higher extent than neuronal Cx36. We conclude that astrocytic gap junctions are key players in the formation of epileptiform activity and we provide a scheme for the different mode of action in the convulsive and non-convulsive epilepsy types.